Izdelava in optimizacija nove tehnologije varjenja pedala za avtomobilsko zavoro - Tušek, Janez (Strojniški vestnik, 2001)
We have developed and optimised a new technology for welding the brake pedal of a motor vehicle that is based on resistance-projection and spot-welding processes. We describe the problems encountered when using arc welding and the reasons for substituting the technology. To aply the new technology we constructed a fixture for the simultaneous clamping of a pedal body, a foot treadle and a stop-swich rest. We then optimised the parameters for the projection welding of a foot treadle and a stop-switch rest. We then optimised the parameters for the projection welding of the foot treadle to the pedal body and the stop-switch rest to the pedal body; we also optimised the resistance spot welding of the other part of the rest to the pedal body. Our costing of the process showed that the substitution of the technology was economically justified since the new technology simplified the manufacture of the motor-vehicle brake pedal.
Keywords: varjenje točkovno; varjenje bradavično; zavore avtomobilske; pedali; varjenje obločno; uporovno varjenje; točkovno varjenje; bradavično varjenje; avtomobilski deli